2016
DOI: 10.1007/s11160-016-9429-y
|View full text |Cite
|
Sign up to set email alerts
|

Maintaining customary harvesting of freshwater resources: sustainable Indigenous livelihoods in the floodplains of northern Australia

Abstract: Freshwater resources underpin multiple livelihood systems around the world, particularly in highly productive tropical floodplain regions. Sustaining Indigenous people's access to freshwater resources for customary harvesting, while developing alternative livelihood strategies can be challenging. The sustainable livelihoods approach was applied to examine the ways in which multiple livelihoods in the East Alligator River floodplain region in northern Australia influence Aboriginal people's access to freshwater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 97 publications
0
9
0
Order By: Relevance
“…Kakadu's floodplains ( Figure 2) are inundated annually during the wet season (Ward et al, 2014) and support a diversity of species including fish, turtles, and waterbirds (Finlayson et al, 2006). Kakadu's Ramsar-listed floodplains provide Indigenous people with foods (plant and animal species native to Australia that are known locally as "bush tucker"), such as magpie goose, fish, and turtles and other materials used for weapons, utensils, weaving, and medicines (Ligtermoet, 2016;McGregor et al, 2010). In a manner common to the human ecology of many north Australian wetlands (Jackson, Finn, & Featherston, 2012), utilization of floodplains enables Kakadu's land-owners to maintain important communal aspects of social and economic life based on cultural continuities.…”
Section: Methodsmentioning
confidence: 99%
“…Kakadu's floodplains ( Figure 2) are inundated annually during the wet season (Ward et al, 2014) and support a diversity of species including fish, turtles, and waterbirds (Finlayson et al, 2006). Kakadu's Ramsar-listed floodplains provide Indigenous people with foods (plant and animal species native to Australia that are known locally as "bush tucker"), such as magpie goose, fish, and turtles and other materials used for weapons, utensils, weaving, and medicines (Ligtermoet, 2016;McGregor et al, 2010). In a manner common to the human ecology of many north Australian wetlands (Jackson, Finn, & Featherston, 2012), utilization of floodplains enables Kakadu's land-owners to maintain important communal aspects of social and economic life based on cultural continuities.…”
Section: Methodsmentioning
confidence: 99%
“…2) and S2E. In this regard, others have found that customary use of natural resources is directly linked to maintaining cultural knowledge, institutions, and biodiversity (e.g., Singh et al 2013, Ligtermoet 2016, Paniagua-Zambrana et al 2016.…”
Section: Promoting Indigenous Wetland Management and "Services To Ecomentioning
confidence: 99%
“…Five of the papers Gould (2016), Ligtermoet (2016), McMillan and Prosper (2016), Rose et al (2016), Schnierer and Egan (2016) focus on Indigenous livelihoods around fish or fisheries resources. All consider the challenges in undertaking traditional harvesting or fisheries management practices under contemporary management regimes, particularly those that give primacy to non-Indigenous fishers and fisheries management methods (Gould, McMillan and Prosper, Schnierer and Egan).…”
Section: A Meeting To Foster Relationships and Understandingmentioning
confidence: 99%
“…All of these papers describe the significant challenges for Indigenous people attempting to reinvigorate culturally appropriate fisheries activities under colonial systems of fisheries governance which have given legal rights to nonIndigenous fishers. Ligtermoet (2016) also explores the challenges of sustaining customary harvest of resources amid contemporary systems of governance. She identifies the circumstances under which livelihoods currently derived from non-customary use of floodplains-including tourism, cattle grazing and biodiversity conservation-support or constrain the maintenance of livelihoods based on the customary harvest of floodplain resources by Bininj in the East Alligator region of northern Australia.…”
Section: A Meeting To Foster Relationships and Understandingmentioning
confidence: 99%